Edukasi Pemeliharaan Kesehatan Gigi pada Anak Usia Sekolah Dasar - Nur Hidayat; Adinda Aulia; Aziizah Fauziyyah; Haris Sidik; Lutfhi Alfian (Yayasan Inspirasi El Burhani, 2023)
Introduction: A child is someone between the ages of 6 and 12 who is ready for school. Children who do not know as much as they should about their teeth and oral health will likely exhibit poor habits when it comes to taking care of their teeth. As a result, they will be more likely to develop dental caries, which can hinder their growth and development. In Indonesia, the prevalence of caries cases is 88.8 percent, and the prevalence of root caries is 56.6% Objective: The purpose of this health counseling is to provide understanding and knowledge about dental health to students at SDN 2 Winduraja, Winduraja Village, Kawali District. Method: This activity used a counselling approach which is carried out by showing a video then reviewing the material again and respondents are given time to ask questions as an evaluation process of the activity. Result: Implementation of this health counseling to students of SDN 2 Winduraja as participants and carried out in schools in order to add insight and be able to bring clean and healthy lifestyle to prevent tooth decay. Conclusion: By conducting health education regarding dental health maintenance education in school-age children it is proven useful for increasing knowledge and preventing damage to teeth.